What financial conditions affect dynamic equity risk factor allocation? - Achim Backhaus; Aliya Zhakanova; Matthias Bausch (Economies, 2022)
The "technology bubble" in the late 1990s, the financial crisis in 2007/2008, and the Eurozone crisis generated significant losses across several asset classes. The objective of this paper is to investigate risk premia factors such as size, value, momentum, carry, quality, and low volatility and their time-variant behavior. The time-variant behavior of these risk premia baskets has been analyzed based on different financial conditions: The business cycle, the yield curve, equity market momentum, and different risk conditions. Factor calculations are based on the MSCI World universe. The monthly data set ranges from January 1995 to September 2017. The results underpin the prevalent observation that equity risk factors consistently outperform the broad market and therefore generate significant alpha. However, the paper shows that a dynamic allocation of risk factors can achieve an attractive return-risk relation. The study shows very clearly how different risk factors behave in different financial conditions and that an allocation to more offensive or more conservative risk factors can outperform a diversified, equally-weighted portfolio.
Keywords: 330; dynamic factor allocation; portfolio construction; risk premia